Revealing Cultural Aspects in Darmanto Jatman’s Poem Istri - Sarif Syamsu Rizal; Jumanto Jumanto; Raden Arief Nugroho (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2022)
The study entitled “Revealing the Cultural Aspects in the poem Darmanto Jatman’s Istri discusses what cultural aspects are in a literary work of the poem. The purpose of this study is to find and prove the cultural aspects in the poem which consists of three aspects, namely the cultural concept, form, and components contained in the poem. The writer conducts a study with a qualitative descriptive model by determining the object of study in a poem text. The result of this study is an interpretative and explorative description of cultural aspects within the textual orientation of a literary work of the poem. The writer applies analytical techniques in literary criticism that prioritizes the terms of reference established by Taylor, Barker, Hoenigmann, and Kluckhohn in proving how well a literary work imitates life by finding cultural aspects in the poem.Keywords: concept; form; component; poem; cultural aspect.